Mechanical properties improvement of Self Compacting Concrete (SCC) using polypropylene fiber - Vera Agustriana Noorhidana Noorhidana; Laksmi Irianti Irianti; Tas'an Junaedi Junaedi (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2021)
SCC (self-compacting concrete) is a type of concrete that can compact itself without the help of external compaction. Thus, it can fill all parts of the formwork that are narrow and have tight reinforcement. A problem that often arises in the use of SCC is the segregation of concrete mixture, which reduces the strength of the concrete. This paper presents the effect of polypropylene fiber on the fresh concrete workability, compressive strength, splitting-tensile strength, and flexural-tensile strength of SCC concrete. The variations of the polypropylene fiber added to the SCC mixture are 0%, 0.05%, 0.067%, 0.1%, and 0.15% of the concrete’s volume, with a water-cement ratio of 0.5 and 0.38 and dense-graded and gap-graded coarse aggregate. Each concrete variation is made into cubes (150x150x150 mm3) for the compressive strength test, cylinders (dia.150mm; height 300mm) for splitting-tensile test, and prisms (100x100x400 mm3) for the flexural-tensile test. The experiments were carried out with concretes with the age of 28 days. The result showed that, polypropylene fiber could reduce the segregation in the SCC concrete mixture. The optimal polypropylene fiber percentage is 0.05%, which could improve the compressive strength by 12.2%, the splitting strength by 17.7%, and flexural strength by 322.3% compared to SCC concrete without polypropylene fiber.